2019
DOI: 10.1080/10447318.2019.1688946
|View full text |Cite
|
Sign up to set email alerts
|

Persona Transparency: Analyzing the Impact of Explanations on Perceptions of Data-Driven Personas

Abstract: Computational techniques are becoming more common in persona development. However, users of personas may question the information in persona profiles because they are unsure of how it was created. This problem is especially vexing for data-driven personas because their creation is an opaque algorithmic process. In this research, we analyze the effect of increased transparencyi.e., explanations of how the information in data-driven personas was producedon user perceptions. We find that higher transparency throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…For both samples, a carefully selected number of participants from the online survey platform Prolific was recruited. Prolific has been used in several persona user studies in the past [ 94 , 96 , 99 , 100 ], and its data quality has been found satisfactory for academic research [ 82 , 83 ]. We applied custom prescreening to increase the validity of the responses with the following sampling criteria: Minimum Age: 23, Maximum Age: 62 (inclusive)—the purpose was to focus on those in active work life United Kingdom, United States, Ireland, Australia, and New Zealand—the purpose was to focus on predominantly English-speaking countries to avoid misunderstanding of the questions Student Status: No—the purpose was to focus on those in active work life Excluding self-employed individuals—the purpose was to focus on people working in organizations larger than one person Employment status: Full-time—the purpose was to focus on people actively engaging in work life on a full-time basis Organizational tenure: excluding those with less than five months—the purpose was to focus on people that have an adequate understanding of their organization; hence a minimum tenure was required.…”
Section: Validation Samples: Quantitative Validation Studiesmentioning
confidence: 99%
“…For both samples, a carefully selected number of participants from the online survey platform Prolific was recruited. Prolific has been used in several persona user studies in the past [ 94 , 96 , 99 , 100 ], and its data quality has been found satisfactory for academic research [ 82 , 83 ]. We applied custom prescreening to increase the validity of the responses with the following sampling criteria: Minimum Age: 23, Maximum Age: 62 (inclusive)—the purpose was to focus on those in active work life United Kingdom, United States, Ireland, Australia, and New Zealand—the purpose was to focus on predominantly English-speaking countries to avoid misunderstanding of the questions Student Status: No—the purpose was to focus on those in active work life Excluding self-employed individuals—the purpose was to focus on people working in organizations larger than one person Employment status: Full-time—the purpose was to focus on people actively engaging in work life on a full-time basis Organizational tenure: excluding those with less than five months—the purpose was to focus on people that have an adequate understanding of their organization; hence a minimum tenure was required.…”
Section: Validation Samples: Quantitative Validation Studiesmentioning
confidence: 99%
“…Initially developed by Cooper (1999) as user personas for software development, teams within Microsoft extended the application and set out foundations which find their application until today (Pruitt and Grudin, 2003). User personas have been extended in various ways, for examples towards future or anti personas (Fergnani, 2019, Fergnani andJackson, 2019;Fuglerud et al, 2020;Miaskiewicz and Kozar 2011;and Salminen et al, 2020). They can be developed in various ways depending on available information, resources and requirements profiles.…”
Section: Persona-based Designmentioning
confidence: 99%
“…Transparency affects credibility (decrease), completeness (increase) and clarity (increase). The persona gender also affects the perceived completeness of the persona by the user, but this was evident only for female personas [32].…”
Section: Related Workmentioning
confidence: 99%